The ability of fungi Achlya & Saprolegnia in Biological Degradation for insecticide Diazinon - Alrikabi, Lamyaa Sabeeh Abdullah; Aboud, D. Majid Kadhim (Al-Qadisiyah Journal of Pure Science, 2017)
The study aimed to investigate the role of tow fungi Saprolegnia sp. & Achlya sp. biological degradation of the insecticide Diazenon which widely used for spraying crops to get protect from insects. Tow fungi were isolated from water of the river Diwaniyah and study their ability in degradation of diazenon , inspected the used different pesticide concetrations is (20,40,60,80 ) part per million and different periods of time ranging between (2, 4, 6, 8) on the estimate of the quantity of pesticide remaining by using the HPLC study was also impact factors other of living biomass of the tow fungi biomass and the temperature and pH has proved the results the ability of lesser fungus Saprolagnia high in degradation of pesticide , which surpassed the ability of Achlya and pointed results to the biomass increase live increase the fungus ability of degradation , especially when 1600 mg , was more than the capacity of the degradation of pesticide either temperature, degree of 30 cÂ° is optimal to degrade pesticide in the optimal value for the pH is at 7 , which gave the best results